Oral frailty and neurodegeneration in Alzheimer's disease - Dibello, Vittorio; Lozupone, Madia; Manfredini, Daniele; Dibello, Antonio; Zupo, Roberta; Sardone, Rodolfo; Daniele, Antonio; Lobbezoo, Frank; Panza, Francesco (Neural regeneration research, 2021)
Frailty is a critical intermediate status of the aging process with a multidimensional and multisystem nature and at higher risk for adverse health-related outcomes, including falls, disability, hospitalizations, institutionalization, mortality, dementia, and Alzheimer's disease. Among different frailty phenotypes, oral frailty has been recently suggested as a novel construct defined as a decrease in oral function with a coexisting decline in cognitive and physical functions. We briefly reviewed existing evidence on operational definitions of oral frailty, assessment and screening tools, and possible relationships among oral frailty, oral microbiota, and Alzheimer's disease neurodegeneration. Several underlying mechanism may explain the oral health-frailty links including undernutrition, sarcopenia linked to both poor nutrition and frailty, psychosocial factors, and the chronic inflammation typical of oral disease. Oral microbiota may influence Alzheimer's disease risk through circulatory or neural access to the brain and the interplay with periodontal disease, often causing tooth loss also linked to an increased Alzheimer's disease risk. On this bases, COR388, a bacterial protease inhibitor targeting Porphyromonas gingivalis implicated in periodontal disease, is now being tested in a double-blind, placebo-controlled Phase II/III study in mild-to-moderate Alzheimer's disease. Therefore, oral status may be an important contributor to general health, including Alzheimer's disease and late-life cognitive disorders, suggesting the central role of preventive strategies targeting the novel oral frailty phenotype and including maintenance and improvement of oral function and nutritional status to reduce the burden of both oral dysfunction and frailty.